The Influence of Government Expenditure Transparency on Public Trust and Economic Growth in Nigeria: A Business Administration Perspective - Oluwayemisi, Ali-Momoh Betty; Ogundele Johnson, Olatunde; Adegun Taiwo, Joshua; Braimoh Omotola, Adejumoke; Ilo Oluwakemi, Alice; Kayode, Bejide Michael; Fabiyi Adekunle, David (Acta Universitatis Danubius. Œconomica, 2024)
This study investigates the relationship between transparency in government expenditure authorization and public trust and economic growth in Nigeria. The study aims to achieve three primary objectives: first, to investigate how the level of accessibility of budgetary information influences public trust, to examine the extent to which public debt transparency influences public trust in government institutions and to analyze the relationship between transparency in disclosing revenue sources and its impact on public trust with a focus on the federal university system in South West Nigeria.. The study's population comprises bursary staff across the six federal universities in south west Nigeria. A sample size of 385 participants was selected using purposive sampling methods. Both quantitative and qualitative research methods were employed, including surveys, interviews, and document analysis. The response rate of questionnaires varies across universities, with a total response rate of 96%, indicating a robust and representative sample for analysis. The findings of the study revealed that the accessibility of budgetary information was found to have a non-significant influence on public trust (coefficient: -0.017131, p-value: 0.0781), public debt transparency has positive and significant influence on public trust with (coefficient: 0.232477, p-value: 0.0000) and transparency in disclosing revenue sources also have positive and significant effect on public trust with (coefficient: 0.654819, p-value: 0.0000) contributing to public trust in government institutions, particularly federal universities. Which is a clear indication that transparency in government expenditure authorization has significant impact on public trust within the federal university system in South West Nigeria. These results emphasize the importance of transparent financial practices in strengthening public trust within government institutions, highlighting the significant impact of transparency in government expenditure authorization on public trust in the federal university system in South West Nigeria.